The Influence of Steam Project-Based Chemistry Learning with the Assistance of Chemsketch on Learning Outcomes and Creative Thinking Ability on Macromolecular Materials - Ummah, Miftahun Nafiul; Nugroho, Deni Ebit (Universitas Sebelas Maret, 2023)
This research aims to determine the effect of STEAM Project-based chemistry learning assisted by ChemSketch on the learning outcomes and creative thinking abilities of students at SMA N 1 Kendal. This research is quantitative research using the Quasi Experimental method. The quasi experimental design in this research is nonequivalent control group design. Samples were taken using cluster random sampling technique. The population of this study was all students in class XII MIPA SMA N 1 Kendal. Chemistry learning using the STEAM Project approach has a moderate effect in improving student learning outcomes as evidenced by the t-test value of the difference between two average learning outcomes of 0.031 (sig. (2 tailed) < 0.05) which means Ha is accepted and the Effect Size test of 0.53. Meanwhile, the STEAM Project approach in this research had no effect on students' creative thinking abilities due to the lack of variety of questions and limited time during learning. This is proven by the t-test, the difference between the two average creative thinking abilities is 0.109 (sig. (2 tailed) > 0.05).